MORRIE SCHWARTZ’S PERSPECTIVES ON AMERICAN VALUES IN MITCH ALBOM’S TUESDAYS WITH MORRIE - TIANI, KARTIKA DARIS (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: American values, perspectives, individualism, materialism, and activity and workValues are abstract concepts used by the society as the orientation in lifestyle, think, act, and so on. In connecting with literary works, they are on which values as intrinsic aspects rely on. That is because literary works are seen as the mirror of the social condit ion, including values. Mitch Albom’s Tuesdays  with Morrie is one of the literary works which contains American values,  especially from Morrie’s point of view as the main character. Those values that appear in the novel are used as the object of the study. In other words, this study disscusses American values from Morrie Schwartz’s perspectives. Through Morrie Schwartz’s idea about American values, this study is wished to give the new yet useful point of view related to the values of life.Sociological approach to literature is used in this study because Tuesdays with Morrie is based on true story which contains real descriptions of American culture and social condition, especially the values.The result of the study reveals that Morrie Schwartz had his own perspectives toward American values. Most of his concern was about the importance of human relation above all values. Those perspectives were delivered through Morrie Schwartz’s opinions, crit icisms, and suggest ions. From this study, it is revealed that Morrie Schwartz had the idea of intimate indivualism, a state of being free to express oneself yet fully consider about relating to others. He also had a thought that material possessions was not the key to happiness, but love within human relationship was. Family and marriage were believed to be the spheres to decreace individualism and materialism. To Morrie Schwartz, growing old was not the limitation for people to be actively productive.Finally, it is suggested to the next researcher to cunduct a study about Morrie Schwartz’s effort in gaining life sat isfact ion by using socio-psycological approach because his efforts (thoughts, feelings, and actions) to reach the goal were so much related to the society.